OSTEOSARCOMA - Jon Hadi (Nusantara Hasana Journal, 2026)
Osteosarcoma is the most common primary malignant bone tumor in children and adolescents, particularly during periods of rapid growth. This tumor originates from mesenchymal cells that produce osteoid or immature bone matrix and commonly affects the metaphyseal regions of long bones, such as the distal femur, proximal tibia, and proximal humerus. The exact etiology of osteosarcoma remains unclear; however, genetic factors, radiation exposure, and certain bone disorders are known to increase the risk of its development. Clinical manifestations typically include progressive bone pain, localized swelling, limited joint movement, and, in some cases, pathological fractures. Diagnosis is established through clinical evaluation, physical examination, radiological imaging, and histopathological confirmation. The management of osteosarcoma requires a multidisciplinary approach involving neoadjuvant chemotherapy, surgical resection of the tumor, and adjuvant chemotherapy. Advances in surgical techniques and chemotherapy regimens have significantly improved patient survival rates. Prognosis is influenced by tumor size, location, response to chemotherapy, and the presence of metastases, particularly to the lungs. Early detection and appropriate treatment are essential to improve patient outcomes and quality of life.